2007
DOI: 10.1159/000107488
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Stable <i>Pseudomonas aeruginosa</i> PseA Protease Gene: Identification, Molecular Characterization, Phylogenetic and Bioinformatic Analysis to Study Reasons for Solvent Stability

Abstract: We have previously isolated a solvent-stable protease from a novel solvent-tolerant strain of Pseudomonasaeruginosa (PseA). Here we report cloning and characterization of the gene coding for this solvent-tolerant protease. A homology search of the N-terminal amino acid sequence of the purified PseA protease revealed an exact match to a P. aeruginosa PST-01 protease gene, lasB. The c-DNA sequence of the PST-01 protease was used to design primers for the amplification of a 1,494-bp open reading frame encoding a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 54 publications
(54 reference statements)
1
6
0
1
Order By: Relevance
“…The N-terminal amino acid residue of mature ME-4 protease (Cheng et al 2009) is located at position 198 of the deduced amino acid sequence, which suggested that ME-4 protease is synthesized as a pre-pro-protein, as previously observed for elastases from P. aeruginosa (Schad et al 1987;Jellouli et al 2008). The sequence of the first 20 N-terminal residues of the 197 amino acid pre-pro-region was similar to the signal peptide sequences of Pseudomonas elastases (BAB79621, AAG07111, and AAZ78231), and was followed by a 177 amino acid pro-peptide (Bever and Iglewski 1998;Gupta et al 2008). The primary structure of the mature region of the ME-4 protease has a high level of identity to the primary structure of elastases from P. aeruginosa: LasB of P. aeruginosa PST-01 (BAB79621, 99% identity, Online Resource 1), LasB of P. aeruginosa PA01 (AAG07111, 99%), and LasB of P. aeruginosa MN7 (AAZ78231, 99%), and similarity (Fig.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…The N-terminal amino acid residue of mature ME-4 protease (Cheng et al 2009) is located at position 198 of the deduced amino acid sequence, which suggested that ME-4 protease is synthesized as a pre-pro-protein, as previously observed for elastases from P. aeruginosa (Schad et al 1987;Jellouli et al 2008). The sequence of the first 20 N-terminal residues of the 197 amino acid pre-pro-region was similar to the signal peptide sequences of Pseudomonas elastases (BAB79621, AAG07111, and AAZ78231), and was followed by a 177 amino acid pro-peptide (Bever and Iglewski 1998;Gupta et al 2008). The primary structure of the mature region of the ME-4 protease has a high level of identity to the primary structure of elastases from P. aeruginosa: LasB of P. aeruginosa PST-01 (BAB79621, 99% identity, Online Resource 1), LasB of P. aeruginosa PA01 (AAG07111, 99%), and LasB of P. aeruginosa MN7 (AAZ78231, 99%), and similarity (Fig.…”
Section: Resultssupporting
confidence: 73%
“…The probe hybridized to 3.2 kb PstI, 5.0-kb EcoRI, and 6.0 kb ClaI fragments (data not shown), which indicated that strain ME-4 carries one gene encoding pre-pro-LasB_ME4. These findings indicate that native ME-4 protease might be identical to one of the Pseudomonas elastases (Gupta et al 2008;Jellouli . 2008).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…They have reported that the disulfide bonds and amino acid residues located on the surface of the molecule play an important role in the organic solvent stability of the enzymes. Gupta et al [35] have proposed that the presence of hydrophobic clusters on the protein surface and disulfide bonds was responsible for A B Figure 3 Optimal temperature (A) and thermal stability (B) of the xylanase from A. tubingensis FDHN1. Xylanase activity was measured at different temperatures to determine its optimal range.…”
Section: Effect Of Organic Solvents On the Activitymentioning
confidence: 99%
“…They reported that disulfide bonds and amino acid residues located on enzyme surface play important roles in organic solvent stability. The structural analysis of P. aeruginosa protease (after treatment with organic solvent) revealed the presence of two disulfide bonds and hydrophobic patches at the protein surface, and was thought to be a key factor for solvent-stable nature of the enzyme [246,247]. Gaur et al [247] carried out bioinformatic analysis to find the structural basis for the solvent tolerant nature of P. aeruginosa PseA aminopeptidase, and found that its primary structure contained 52% hydrophobic residues (folded in a conformation that favored its stability in organic solvents).…”
Section: Solvent Tolerance Strategies Of Microbes and Their Enzymesmentioning
confidence: 99%